Efforts by the Patrol Unit of the Samapta Division of Jepara Police to Prevent Motor Vehicle Theft Crimes in Jepara Regency. - Muhammad Abel Putra Mirzan (Tanggon Kosala, 2023)
The author raises the final task with the problem "Efforts of the Patrol Unit of the Jepara Police Samapta Unit in Preventing Pawnshop Crime in the Jepara Regency Area". This final project uses a qualitative approach with a descriptive analytical research method. The background of this Final Project is the high rate of theft in the jurisdiction of the Jepara Police. Fluctuations in theft that occur need to be prevented in order to create security and order, therefore the Polri operational unit which is assigned the task of prevention and community service must be the top priority for Samapta members. This study aims to describe the efforts of the Patrol Unit of the Jepara Police Samapta Unit in preventing theft which is associated with several factors that influence patrol efforts and to describe the efforts made by the Jepara Police Samapta Unit in preventing theft. This final project uses management theory and SWOT. Efforts made by the Samapta Patrol Unit organization in preventing the criminal act of theft are connected with the elements in the management theory used, namely consisting of Man, Money, Material, Machine, Method and Market. In the second formulation of the problem is about the implementation efforts by the patrol unit in preventing theft associated with the theory used by the author is with the theory of management, namely planning, organizing, implementing and controlling. As well as used the SWOT theory to describe the results of the factors that influence the initial conditions, namely internal factors and external factors. Internal factors such as there are still reports that are not in accordance with implementation, lack of personnel competency in the patrol section, and shortage of patrol unit personnel. While external factors such as the negligence of the community to maintain their vehicles. Suggestions related to the efforts of the Samapta Patrol Unit in preventing cases of theft are by adding personnel, increasing the implementation of appeals to the public regarding the rampant cases of theft, and increasing the quality of members as the implementation of patrol activities.